Ryan-Holmes and modified Ryan-Holmes processes for LNG production - Lastari, Fonny (Curtin University, 2009)
The objective of this research was to evaluate various process alternatives for the production LNG (Liquefied Natural Gas) from natural gas feeds with significant CO2 levels, typical of some of the Australian gas reserves. It is believed that the conventional amine process which is commonly utilized for treating sour natural gas may be energy-intensive, particularly if CO2 produced must be sequestrated. Consequently, two different alternatives to the amine process were investigated, which were based on the Ryan-Holmes (RH) process with one of them also using membrane in addition to distillation columns.